Instant cereals enriched with carboxylates - A. Shaimerdenova, D; M. Chakanova, Zh; Zh. Sultanova, M; Yu. Borovsky P. R, A; ., Shaimerdenova; A. Abdrakhmanov, Kh. (International Journal of Engineering and Technology, 2018)
The article presents the developed technology for obtaining cereal products of rapid cooking with increased nutritional value, enriched with micronutrients, for which wheat, rice, corn and buckwheat served as raw materials. The food and biological value of the obtained instant cereals is studied, as well as the study of the effect of micronutrients-carboxylates of food acids on technological, food and consumer indices. As a result of the research, 4 prescriptions were chosen with the highest growth of micro and microelements.Â Â